Detection Of Birth Defects Through Early Perinatal Screening: Experience Of Developing Countries (Texas Journal of Medical Science, 2026)
This article provides a scientific analysis of the importance of early perinatal screening in the detection of birth defects, the level of its application in developing countries, and systemic problems. The study examined the effectiveness of prenatal diagnostic methods, infrastructural and personnel constraints in the healthcare system, as well as socio-cultural factors. In addition, the possibilities of modernizing the screening system based on artificial intelligence and digital technologies were assessed. The results show that by improving the screening system, it is possible to significantly improve maternal and child health indicators.